2022
DOI: 10.1177/23743735221107241
|View full text |Cite
|
Sign up to set email alerts
|

Group Telehealth Music Therapy With Caregivers: A Qualitative Inquiry

Abstract: Informal caregivers of older adults are faced with increased responsibilities as health and social systems fail to respond to the rising demands associated with the aging populations. For many caregivers, the COVID-19 pandemic has severely impacted their access to already sparse supportive resources, highlighting the importance of varying service delivery methods to meet caregivers’ needs. This qualitative study explored the experiences of informal caregivers of older adults who took part in group telehealth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…These consequences of caring for health must be addressed from a multidisciplinary approach, considering the needs of the informal caregiver. Many therapeutic disciplines can be used to improve their well-being ( Warth et al, 2019 ; Ahn et al, 2020 ), with music therapy being a very powerful tool, demonstrating effectiveness in improving the QoL of informal caregivers ( Clair et al, 1993 ; Clair, 2002 ; Brotons and Marti, 2003 ; Magill, 2009 ; Choi, 2010 ; Kim and Dvorak, 2018 ; Potvin et al, 2018 ; Gok Ugur et al, 2019 ; García-Valverde et al, 2020 ; Valero-Cantero et al, 2020 ; Wilhelm and Wilhelm, 2020 ; Brault and Vaillancourt, 2022 ; Denk, 2023 ; Whitford et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These consequences of caring for health must be addressed from a multidisciplinary approach, considering the needs of the informal caregiver. Many therapeutic disciplines can be used to improve their well-being ( Warth et al, 2019 ; Ahn et al, 2020 ), with music therapy being a very powerful tool, demonstrating effectiveness in improving the QoL of informal caregivers ( Clair et al, 1993 ; Clair, 2002 ; Brotons and Marti, 2003 ; Magill, 2009 ; Choi, 2010 ; Kim and Dvorak, 2018 ; Potvin et al, 2018 ; Gok Ugur et al, 2019 ; García-Valverde et al, 2020 ; Valero-Cantero et al, 2020 ; Wilhelm and Wilhelm, 2020 ; Brault and Vaillancourt, 2022 ; Denk, 2023 ; Whitford et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the few existing studies about music therapy and informal caregivers, songwriting is the most used technique. The studies that focused on the applications of music therapy in group formats with informal caregivers have shown a positive impact on QoL ( Clair et al, 1993 ; Clair, 2002 ; Brotons and Marti, 2003 ; Magill, 2009 ; Choi, 2010 ; Kim and Dvorak, 2018 ; Potvin et al, 2018 ; Gok Ugur et al, 2019 ; Clark et al, 2020 ; García-Valverde et al, 2020 ; Valero-Cantero et al, 2020 ; Wilhelm and Wilhelm, 2020 ; Brault and Vaillancourt, 2022 ; Denk, 2023 ; Whitford et al, 2023 ). However, most studies focus on the intervention of the caregiver and cared-for person dyad.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, despite being conducted pre-COVID-19 pandemic, and a number of studies investigating the effectiveness of online music therapy interventions (Baker & Tamplin, 2021; Brault & Vaillancourt, 2022; Clements-Cortes et al, 2021; Cole et al, 2021; Kantorova et al, 2021; Lee et al, 2021; Wilhelm & Wilhelm, 2022), our research fills a gap by focusing on the experience of the client and takes into account technical difficulties within their experiences. In contrast, current VMT research focuses mostly on the experiences of the therapists (Baker & Tamplin, 2021; Clements-Cortes et al, 2021; Cole et al, 2021; Lee et al, 2021; Wilhelm & Wilhelm, 2022), except for a few that focus on the experiences of clients (Baker & Tamplin, 2021; Brault & Vaillancourt, 2022). Thus, our research provides insight into the perspectives of older adults in the online medium.…”
Section: Discussionmentioning
confidence: 99%
“…Results demonstrated that music therapists across North America (Cephas, Sofield, & Millstein, 2022; Clements-Cortes, Mercadal-Brotons, Silva, & Moreira, 2021; Cole et al, 2021; Gaddy et al, 2020; Kantorova et al, 2021; Knott & Block, 2020) and internationally (Agres, Foubert, & Sridhar, 2021; Baker & Tamplin, 2021) did adapt their practices to virtual delivery and that, in general, the majority found the benefits outweighed the challenges (Baker & Tamplin, 2021; Cole et al, 2021; Kantorova et al, 2021). Most studies focused on effectiveness from the music therapist’s perspective (Baker & Tamplin, 2021; Clements-Cortes et al, 2021; Cole et al, 2021; Lee, O’Neill, & Moss, 2021; Wilhelm & Wilhelm, 2022) while only few focused on clients’ perceptions of the experience (Baker & Tamplin, 2021; Brault & Vaillancourt, 2022). Clements-Cortes et al (2021), Lee et al (2021), and Wilhelm and Wilhelm (2022) focused on VMT with older adults and discovered a mix of both opportunities and challenges, however, only from the perspective of the music therapist.…”
Section: Introductionmentioning
confidence: 99%
“…However, online meeting platforms can be excellent for engaging with music in an aural form, simply by listening to it. Very few studies have been conducted on online music therapy in general ( Brault and Vaillancourt, 2022 , Brunick, 2021 , Cephas et al, 2022 ; Cole at al., 2021; Deogharia, 2020 ; Molyneux et al, 2020 ; Rodriguez, 2022 ) and most of them discuss the advantages, disadvantages, and complexity in running online music therapy sessions. Clearly, online music therapy is something that needs to be done but requires more learning, experience, expertise, and online meeting platforms that are more sophisticated than what is currently available.…”
Section: Introductionmentioning
confidence: 99%